2019
DOI: 10.1007/s00441-019-03111-w
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a consequence of seasonal functions of testis and epididymis in adult male European bison (Bison bonasus, Linnaeus 1758)

Abstract: The European bison is still an animal endangered with extinction, so by learning factors that regulate its reproduction, we can contribute to the survival of this species. On the other hand, autophagy is a dynamic, lisosomal, and evolutionary conserved process which is essential for animal cell survival, homeostasis, and differentiation. This process was demonstrated in many species and in many organs; however, information on the metabolic course of autophagy in the male reproductive system in seasonally repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A densitometric analysis was performed using GelQuantNET software. The bands were quantified and normalized to their corresponding β-actin bands [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…A densitometric analysis was performed using GelQuantNET software. The bands were quantified and normalized to their corresponding β-actin bands [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Protein extraction and Western blot analysis were performed as described by Tabecka-Lonczynska et al. (2020) with some modification [ 23 ]. Briefly, 30 µg of testicular tissue homogenates were separated by using 10% SDS-PAGE electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…During the breeding stage of testicular recovery, the expression of BECN1 and LC3 began to increase in South American plains vizcacha [47]. Tabecka-Lonczynska et al observed an increase in beclin1 and LC3 synthesis and con rmed the function of autophagy in adult reproductive male European bison [45]. Up-regulated expressions of BECN1 and LC3 suggests the increased demand for maintaining homeostasis in male giant pandas during the period of reproductive activity.…”
Section: Innate Immune Changesmentioning
confidence: 99%